The Influence of Transformational Leadership Style and Work Life Balance on Employee Creativity at CV Palem Craft Yogyakarta - Febrianti, Dian Cita; Samsudin, Mohammad Agus (Dinasti International Journal of Management Science, 2025)
This study aims to examine the influence of transformational leadership style and work life balance on employee creativity at CV Palem Craft Yogyakarta, a micro, small, and medium enterprise in the handicraft sector. The employed method was quantitative, utilizing a census techniquethat encompassed all 40 employees of the company. Data was collected through questionnaires and processed with multiple linear regression along with statistical test of validity and reliability. The findings indicated that transformational leadership style and work life balance positively affect employee creativity, however the effect are not statisticaly significant. The transformational leadership style accounts for 5.3% of the variation in creativity, whereas work-life balance aacounts for 9.6%. Concurrently, these variables lack a significant impact on employee creativity, suggesting the presence of other factors that are more influential in shaping creativity. This study indicates the necessity of formulating more effective leadership strategies and work-life balance policies to foster creativity in the creative MSME environment. This study offers a significant overview of the correlation between leadership style, work-life balance, and employee creativity within the local handicraft sector, while also serving as a reference for organizational management and future research in human resource management and the advancement of employee creativity.